Mineralization of Azo Dye from Aqueous Solution via Electro-Activated Persulfate: A Case Study on Direct Red 89 - Behnam Hatami; Arezo Rezaie; Maryam Malekbala (Journal of Environmental Health and Sustainable Development)
Introduction: In recent years, azo dyes, which are widely used in various industries, have attracted attention because of their high production volume, toxicity, and environmental persistence. Advanced oxidation processes (AOPs) have emerged as promising alternatives for the degradation of pollutants by generating reactive radicals. This study investigated the degradation of Direct Red 89 (DR 89) using the electrochemical/persulfate (EC/PS) process. Materials and Methods: A controlled laboratory experiment was conducted utilizing a 1000 mL electrolytic reactor, which was equipped with aluminum and iron electrodes serving as the anode and cathode, respectively. The reactor contained 500 mL of solution, which was continuously stirred using a magnetic stirrer. Sodium hydroxide (NaOH) and hydrochloric acid (HCl) were used to adjust the pH, while sodium chloride (NaCl) served as the supporting electrolyte. The concentration of DR 89 in the samples was measured using a UV-visible spectrophotometer. Results:  The investigation of operational parameters, including pH, reaction time, persulfate concentration, current density, initial dye concentration, and electrolyte concentration, indicated that a maximum removal efficiency of 99.43% was achieved under the optimal conditions: pH 4.0, reaction time of 25 min, current density of 1 mA/cm², electrolyte concentration of 250 mg/L, and persulfate concentration of 30 mg/L, for an aqueous solution containing 80 mg/L of DR89 dye. Conclusion: Compared with other advanced oxidation processes, this approach is more environmentally friendly, with high efficiency, and less pollutant production. Therefore, it can be widely used to treat industrial wastewater containing persistent pollutants.